2010
DOI: 10.3851/imp1722
|View full text |Cite
|
Sign up to set email alerts
|

Viral Clearance and Inflammatory Response Patterns in Adults Hospitalized for Pandemic 2009 Influenza A(H1N1) Virus Pneumonia

Abstract: In severe 2009 H1N1 pneumonia, viral clearance is slow with treatment, particularly in the lower respiratory tract. A more sustained antiviral regime appears warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
153
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(160 citation statements)
references
References 39 publications
4
153
0
3
Order By: Relevance
“…This early proinflammatory burst of cytokines is reminiscent of the hypercytokinemia observed in some animal models of severe infection and humans infected with A (H5N1) viruses (9,12,22). Previous studies focusing exclusively on hospitalized patients with influenza infection found positive associations between serum IL-6, IL-8, MCP-1, and IP-10 levels and clinical severity (10,11,13,23), whereas others showed no differences, possibly because of the restricted nature of their cohorts (24)(25)(26)(27). The association shown here was independent of existing immunity as determined by protective neutralization antibody titer.…”
Section: Discussionmentioning
confidence: 99%
“…This early proinflammatory burst of cytokines is reminiscent of the hypercytokinemia observed in some animal models of severe infection and humans infected with A (H5N1) viruses (9,12,22). Previous studies focusing exclusively on hospitalized patients with influenza infection found positive associations between serum IL-6, IL-8, MCP-1, and IP-10 levels and clinical severity (10,11,13,23), whereas others showed no differences, possibly because of the restricted nature of their cohorts (24)(25)(26)(27). The association shown here was independent of existing immunity as determined by protective neutralization antibody titer.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the sensitivity of RIDTs tended to be lower in cases with pneumonia has serious clinical implications and should warrant further study. There are increasing reports of false-negative test results for upper respiratory samples in influenza patients who developed pneumonia (21), even with the use of PCR assays. Because of a relatively low level of viral shedding in the upper respiratory tract, obtaining a lower respiratory tract sample (e.g., sputum, tracheal aspirate, or bronchoalveolar lavage specimens) for testing is generally advisable (5,22).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL16 is produced by several cell types including dendritic cells (21), lymphocytes (56), vascular smooth muscle cells (52), bone marrow stromal cells (40), tumor cells (35,36), and cardiac tissue (58). SR-PSOX/CXCL16 expression in endothelial cells is upregulated by proinflammatory cytokines, such as TNF-␣ or IFN-␥ (1,25), known mediators of inflammation and ischemia (46,50).…”
Section: Discussionmentioning
confidence: 99%